Effect of Vibhitaki Kshara Sootra in Pilonidal Sinus (International Journal of Ayurveda and Pharma Research, 2025)
Pilonidal sinus is a common source of morbidity and loss of work productivity in healthy young adults. Typically, patients present with a chronic sinus about the level of 1st piece of coccyx. The most commonly used surgical techniques for this condition include excision and primary closure, excision with reconstructive flap. But because of risk of recurrence and infections, an effective treatment is much needful. Pilonidal sinus closely related with description of Salyaja nadivrana, treatment in Ayurveda includes management through Kshara sootra therapy. Kshara is superior to surgical or para surgical techniques. Teekshna guna of Kshara help in Vrana sodhana and promotes faster granulation Kshara sootra indicated in Krisa, Durbala and Bheeru has the capacity to cut the track mechanically and potentially dissolves fibrous tissue creating a healthy base for healing. The present case study deals with effect of Vibhitaki kshara sootra in pilonidal sinus. A 22-year-old female patient with 3 months history of pus discharge at natal cleft managed with Vibhitaki kshara sootra. The initial complaints of pain associated with pus discharge subsided within seven days, while complete cutting of tract observed within 1 month and healing within 2 months. Properties of Vibhitaki like Kashaya rasa, Ushna veerya, Madhura vipaka, Ruksha and Laghu guna which are favourable for the qualities of Kshara. It is also cost effective due to easy availability.